Β2‐Adrenoceptor agonist profiling reveals biased signalling phenotypes for the β2‐adrenoceptor with possible implications for the treatment of asthma. (19th July 2022) - De Pascali, Francesco; Ippolito, Michael; Wolfe, Emily; Komolov, Konstantin E.; Hopfinger, Nathan; Lemenze, Douglas; Kim, Nicholas; Armen, Roger S.; An, Steven S.; Scott, Charles P.; Benovic, Jeffrey L.
Abstract : Background and Purpose: β‐Adrenoceptor agonists relieve airflow obstruction by activating β2 ‐adrenoceptors, which are G protein‐coupled receptors (GPCRs) expressed on human airway smooth muscle (HASM) cells. The currently available β‐adrenoceptor agonists are balanced agonists, however, and signal through both the stimulatory G protein (Gs )‐ and β‐arrestin‐mediated pathways. While Gs signalling is beneficial and promotes HASM relaxation, β‐arrestin activation is associated with reduced Gs efficacy. In this context, biased ligands that selectively promote β2 ‐adrenoceptor coupling to Gs signalling represent a promising strategy to treat asthma. Here, we examined several β‐adrenoceptor agonists to identify Gs ‐biased ligands devoid of β‐arrestin‐mediated effects. Experimental Approach: Gs ‐biased ligands for the β2 ‐adrenoceptor were identified by high‐throughput screening and then evaluated for Gs interaction, Gi interaction, cAMP production, β‐arrestin interaction, GPCR kinase (GRK) phosphorylation of the receptor, receptor trafficking, ERK activation, and functional desensitization of the β2 ‐adrenoceptor. Key Results: We identified ractopamine, dobutamine, and higenamine as Gs ‐biased agonists that activate the Gs /cAMP pathway upon β2 ‐adrenoceptor stimulation while showing minimal Gi or β‐arrestin interaction. Furthermore, these compounds did not induce any receptor trafficking and had reduced GRK5‐mediated phosphorylation of the β2 ‐adrenoceptor. Finally, we observed minimal physiological desensitization of the β2 ‐adrenoceptor in primary HASM cells upon treatment with biased agonists. Conclusion and Implications: Our work demonstrates that Gs ‐biased signalling through the β2 ‐adrenoceptor may prove to be an effective strategy to promote HASM relaxation in the treatment of asthma. Such biased compounds may also be useful in identifying the molecular mechanisms that determine biased signalling and in design of safer drugs.